MEDB-66. Investigating intra-tumoral heterogeneity of extrachromosomal DNA in SHH medulloblastoma. (3rd June 2022) - Chapman, Owen; Sridhar, Sunita; Wechsler-Reya, Robert J; Chavez, Lukas; Mesirov, Jill P
Abstract: Extrachromosomal circular DNA (ecDNA) is an important driver of aggressive cancers, including medulloblastoma (MB), the most common malignant pediatric brain tumor. Our study's aim is to better understand how ecDNA containing cells can potentiate malignant growth. EcDNA's role in the development of treatment resistance and association with poor outcomes is hypothesized to arise from its contribution to intra-tumoral heterogeneity and its potential to promote oncogene dependency switching. To analyze the intra-tumoral distribution of ecDNA, we have now simultaneously analyzed the accessible chromatin and gene expression in single cells of a SHH medulloblastoma (MB) patient using multiome single-cell ATAC-seq and gene expression (10X Genomics). Whole genome sequencing (WGS) of this tumor previously revealed a heterozygous somatic TP53 mutation and two distinct ecDNAs: a 3.2Mbp amplicon comprising 3 regions of chr1 and another 4.5Mbp amplicon comprising 23 segments originating from chr7 and chr17. We then used multimodal analysis to describe the tumor cell types, gene expression, variant signatures and estimate ecDNA copy number in the medulloblastoma tumor sample. We identified 12 distinct clusters in the human tumor, 5 of which were determined to be normal non-tumor [OSC1] cells, as identified by specific cell type markers, and 7 of which were determined to be tumor cells. Enrichment of ecDNA was restricted to only one of these tumor clusters. In addition, we also performed the same multiome single-cell analyses in an orthotopic xenograft mouse model derived from this SHH MB patient tumor. In the PDX, 17 clusters were identified, all of which were determined to be tumor cells and enriched for ecDNA. Our preliminary results indicate that tumor cells with ecDNA in the human tumor (particularly the ecDNA enriched cluster) almost exclusively account for [OSC2] the cells in the corresponding PDX, emphasizing the aggressiveness of ecDNA containing cells.